On the interaction between welding residual stresses: a numerical and experimental investigation - Salerno, Gervasio; Bennett, Chris; Sun, Wei; Becker, Adib; Palumbo, Nunzio; Kelleher, Joe; Zhang, Shu Yan (Elsevier, 2018)
The interaction of weld induced residual stresses in an important issue for multi-pass and repair welding operations; effective prediction of the magnitude and location of peak residual stresses can lead to improved lifing predictions and greater understanding of the performance of components in service. However, the interaction of existing residual stress field with new ones imposed by fusion welding processes has received little attention to date. This study presents a numerical and experimental investigation into the interaction of bead-on-plate welds in thick plates of IN718 with the aim of evaluating the effects of pre-existing weld residual stresses on the final global residual stress distribution. Sequentially coupled thermo-mechanical finite element (FE) models, which have been validated through temperature measurements, optical macrography and residual stress measurements, performed using the neutron diffraction technique, have been used to investigate the interactions. The results show good correlation between the experimental and model residual stress fields, demonstrating that the FE models are capable of predicting the redistribution of existing residual stress fields subjected to fusion welding processes and that this can be achieved with the use of parent material properties throughout, without considering any material property modifications which may occur due to microstructural changes in and around the weld region. It can also be seen from the results that, even with the relatively thick plates used in the study, a plane-stress state exists in the plates with a normal stress of approximately zero in all cases.